Impact of river dynamics on the genetic variation of Gypsophila repens (Caryophyllaceae): a comparison of heath forest and more dynamic gravel bank populations along an alpine river - Reisch, C.; Sattler, J.; Byers, D. (Plant biology (Stuttgart, Germany), 2021)
Alpine rivers are, despite anthropogenic water flow regulation, still often highly dynamic ecosystems. Plant species occurring along these rivers are subject to ecological disturbance, mainly caused by seasonal flooding. Gypsophila repens typically grows at higher altitudes in the Alps, but also occurs at lower altitudes on gravel banks directly along the river and in heath forests at larger distances from the river. Populations on gravel banks are considered non‐permanent and it is assumed that new individuals originate from seed periodically washed down from higher altitudes. Populations in heath forests are, in contrast, permanent and not regularly provided with seeds from higher altitudes through flooding. If the genetic structure of this plant species is strongly affected by gene flow via seed dispersal, then higher levels of genetic diversity in populations but less differentiation among populations on gravel banks than in heath forests can be expected. In this study, we analysed genetic diversity within and differentiation among 15 populations of G. repens from gravel banks and heath forests along the alpine River Isar using amplified fragment length polymorphisms (AFLP). Genetic diversity was, as assumed, slightly higher in gravel bank than in heath forest populations, but genetic differentiation was, in contrast to our expectations, comparable among populations in both habitat types. Our study provides evidence for increased genetic diversity under conditions of higher ecological disturbance and increased seed dispersal on gravel banks. Similar levels of genetic differentiation among populations in both habitat types can be attributed to the species' long lifetime, a permanent soil seed bank and gene flow by pollinators among different habitats/locations. Genetic variation of Gypsophila repens along an alpine river depends on ecological disturbance by flooding.